2007
DOI: 10.1042/bj20061797
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of binding sites for NF-κB and C/EBPs in IκB-ζ-mediated transcriptional activation

Abstract: IκB-ζ [inhibitor of NF-κB (nuclear factor κB) ζ ] is a nuclear protein that is induced upon stimulation of TLRs (Toll-like receptors) and IL (interleukin)-1 receptor. IκB-ζ harbours Cterminal ankyrin repeats that interact with NF-κB. Our recent studies have shown that, upon stimulation, IκB-ζ is essential for the induction of a subset of inflammatory genes, represented by IL-6, whereas it inhibits the expression of TNF (tumour necrosis factor)-α. In the present study, we investigated mechanisms that determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 46 publications
8
63
0
Order By: Relevance
“…IκBζ has previously been demonstrated to be highly expressed in Th17 cells, dendritic cells, and macrophages upon TLR stimulation, whereas IκBζ is barely detectable in resting cells (18,31). In agreement with a previous study (10), we found that IκBζ was highly expressed in human keratinocytes upon IL-17A stimulation, whereas TNFα stimulation had only a minor effect on IκBζ expression.…”
Section: Discussionsupporting
confidence: 82%
“…IκBζ has previously been demonstrated to be highly expressed in Th17 cells, dendritic cells, and macrophages upon TLR stimulation, whereas IκBζ is barely detectable in resting cells (18,31). In agreement with a previous study (10), we found that IκBζ was highly expressed in human keratinocytes upon IL-17A stimulation, whereas TNFα stimulation had only a minor effect on IκBζ expression.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, overexpression of NFKBIZ in HT1080 cells resulted in elevated IL8 transcription, indicating a role for NFKBIZ. This interpretation is further supported by a recent report showing that NFKBIZ binds and acts on a composite or adjacent C/EBP-NF-kB site almost identical to the site investigated in this study (Matsuo et al, 2007).…”
Section: Fus-ddit3 Deregulates Nf-jb Target Genessupporting
confidence: 91%
“…39 Among the genes induced by P. gingivalis LPS is I B␣, which can re-exert control over NF-B, along with I B ⑀ and particularly, I B , which binds to NF-B p50 in the nucleus and has both negative (IL-8, TNF-␣) and positive (IL-6, IL12p40, GM-CSF, G-CSF) regulatory actions. 40,41 Although rapid NF-B activation is necessary for host defense against microbial invasion, failure to re-exert control with persistent NF-B activation may result in tissue injury, and in the extreme, to organ failure, systemic disease, and death. 42,43 NF-B-responsive genes, including abundant chemokines, were up-regulated both transcriptionally and at the protein level, consistent with rapid mobilization and accumulation of innate and/or adaptive immune cells at the site of P. gingivalis infection and release of cell wall components.…”
Section: Discussionmentioning
confidence: 99%